2022
DOI: 10.3389/fgene.2022.974740
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the expression of N6-methyladenosine RNA methylation regulators in pulmonary artery hypertension

Abstract: Background: Pulmonary arterial hypertension (PAH) is a progressive disease characterized by pulmonary vascular remodeling. The development of PAH involves N6-methyladenosine (m6A) modification. However, the functional role of m6A regulators in PAH and the underlying regulatory mechanisms remain unknown so far.Methods: Microarray data (GSE149713) for monocrotaline induced PAH (MCT-PAH) rat models were downloaded and screened for differentially expressed genes (DEGs) and m6A regulators. Next, we screened for dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…A deeper understanding of PH mechanisms contributes to innovative and effectivetreatments [ 1 ]. In the past two years, studies have found RNA epigenetic modification, especially m6A methylation modification, plays an important role in the PH occurrence and deterioration [ 26 , 27 ].However, less is known about the effect of m6A regulators in mediating PH-associated vascular remodeling, especially, via regulating endothelial cell dysfunction. We explored the expression profiles in PAECS between SuHx PH mouse models and controls using single-cell sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“…A deeper understanding of PH mechanisms contributes to innovative and effectivetreatments [ 1 ]. In the past two years, studies have found RNA epigenetic modification, especially m6A methylation modification, plays an important role in the PH occurrence and deterioration [ 26 , 27 ].However, less is known about the effect of m6A regulators in mediating PH-associated vascular remodeling, especially, via regulating endothelial cell dysfunction. We explored the expression profiles in PAECS between SuHx PH mouse models and controls using single-cell sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the regulation of RNA methylation in diseases has been studied with m 6 A and m 5 C. M 5 C methylation can regulate tumor microenvironment infiltration characterization of lung adenocarcinoma and immune microenvironment of multiple myeloma (60,61). Interestingly, the m 6 A modulator may be a promising biomarker for the diagnosis and treatment of PAH in the monocrotaline-induced pulmonary hypertension model of rats (62)(63)(64). Currently, there is very little research on the effect of m 7 G methylation on PAH.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic process of m6A methylation involves several key proteins, including methyltransferases and demethylases 24,25 . Recent studies have shown that m6A methylation plays a role in chronic obstructive pulmonary disease, pulmonary brosis, lung cancer, and other diseases 26,27 . However, the role of m6A methylation in ALI has not been properly examined.…”
Section: Discussionmentioning
confidence: 99%